COVID-19 related difficulties and perceived coping among university and college students: the moderating role of media-related exposure and stress. Issue 1 (1st January 2021) - Pat-Horenczyk, Ruth; Bergman, Yoav S.; Schiff, Miriam; Goldberg, Alon; Cohen, Ayala; Leshem, Becky; Jubran, Hisham; Worku- Mengisto, Wovit; Berkowitz, Ruth; Benbenishty, Rami
ABSTRACT: Background : University and college students are not usually identified as a population at risk during the COVID-19 pandemic. Yet, there is growing evidence of their specific distress associated with facing multiple abrupt changes and the need for rapid adaptation to a variety of academic, social, and financial challenges. The extent of their exposure to COVID-19 media and the associated media-related stress may further impair students' perceived coping. Objective : This study assessed COVID-19-related functional difficulties and perceived coping among higher education students in Israel and explored the moderating role played by media coverage of the pandemic in inducing stress and exacerbating COVID-19-related difficulties in perceived coping among students. Method : Data was collected from 7, 446 students from seven academic centres in Israel through online questionnaires about four to six weeks after the outbreak of the pandemic in Israel. Results : The findings showed positive associations between COVID-19-related difficulties, media exposure, media-related stress, and decreased levels of perceived coping with the pandemic. Moreover, media-related stress (but not the level of media exposure) moderated the relationship between COVID-19-related difficulties and perceived coping: the associations were significantly stronger for students reporting high media-related stress in comparison to individuals reporting low media-related stress. Conclusions : These results highlight the specific role of media-related stress and the need to distinguish this risk factor from the global impact of exposure to media coverage. The need for self-monitoring of the subjective level of stress associated with media exposure should be part of the psychoeducation efforts provided by public health authorities for promoting self-care during the COVID-19 pandemic. HIGHLIGHTS: This study assessed COVID-19-related functional difficulties and perceived coping among 7, 446 higher education students and explored the moderating role played by media coverage of the pandemic in inducing stress and exacerbating COVID-19-related difficulties in perceived coping.